Accurate modeling of equal-distance spiral bevel gear and the trial production by metal powder injection molding process - LIU Ganhua; TANG Naifu; WANG Qi (Fenmo yejin jishu)
As a new type of bevel gear, the equal-distance spiral bevel gear is suitable for the mass production by metal powder injection molding (MIM) due to the characteristic as the normal equal-distance of spiral tooth surface. According to the coordinate transformation theory, the parametric equations of spherical involute and equal-distance conical spiral curves were derived. The mathematical model of tooth surface was established by the formation principle of tooth surface. The mathematical model of tooth surface was programmed by MATLAB to calculate the coordinates of discrete points on tooth surface, and the accurate modeling of equal-distance spiral bevel gear was completed by reverse engineering of UG. The meshing contact of equal-distance spiral bevel gear was simulated to obtain the transmission performance in ANSYS. Finally, the trial production of equal-distance spiral bevel gear was completed base on the MIM process. In the results, the mathematical model of tooth surface combined with the inverse modeling of discrete points can ensure the accuracy of 3D model, and MIM process can be used to produce the equal-distance spiral bevel gears for mass production.